2021
DOI: 10.3390/jcm10071418
|View full text |Cite
|
Sign up to set email alerts
|

Working towards an ERAS Protocol for Pancreatic Transplantation: A Narrative Review

Abstract: Enhanced recovery after surgery (ERAS) initially started in the early 2000s as a series of protocols to improve the perioperative care of surgical patients. They aimed to increase patient satisfaction while reducing postoperative complications and postoperative length of stay. Despite these protocols being widely adopted in many fields of surgery, they are yet to be adopted in pancreatic transplantation: a high-risk surgery with often prolonged length of postoperative stay and high rate of complications. We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 230 publications
(274 reference statements)
0
7
0
Order By: Relevance
“…[2][3][4] The low return-to-theatre rate from this service evaluation could be attributed to the better recipient and donor selections, organ preservation, back-table preparation, graft placement, and exocrine drainage techniques. 5 The gradual fall in critical care LOS of patients was likely a reflection of the application of the enhanced recovery principles and iCOUGH (incentive spirometry, coughing, oral hygiene, understanding, getting out of bed, head-of-bed elevation) to patients following major surgery. 6 The 4-year data suggested that most patients were either extubated or nearly ready for extubation by the time of their critical care admission.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] The low return-to-theatre rate from this service evaluation could be attributed to the better recipient and donor selections, organ preservation, back-table preparation, graft placement, and exocrine drainage techniques. 5 The gradual fall in critical care LOS of patients was likely a reflection of the application of the enhanced recovery principles and iCOUGH (incentive spirometry, coughing, oral hygiene, understanding, getting out of bed, head-of-bed elevation) to patients following major surgery. 6 The 4-year data suggested that most patients were either extubated or nearly ready for extubation by the time of their critical care admission.…”
Section: Discussionmentioning
confidence: 99%
“…They recommend against excess fluid administration, 14 although there is no evidence to support the use of restricted fluid regimens such as goal-directed fluid therapy. 10 As with the general surgical population, avoiding nasogastric tube placement in pancreatic transplant recipients resulted in a decreased hospital length of stay without resulting in other complications. 15 Postoperatively, early resumption of enteral nutrition is recommended.…”
Section: Pancreas Transplantation (Table 1)mentioning
confidence: 99%
“…Elango and Papalois published a review outlining an ERAS protocol for patients undergoing pancreas transplantation. 10 Preoperatively, they stressed the importance of (1) prehabilitation, including weight loss and smoking cessation, (2) coagulation testing using thromboelastography, and (3) evaluation of iliac arterial calcification with non-contrast computed tomography scan. Intraoperatively, they discussed a standardized antibiotic protocol with a first-generation cephalosporin for 96 hours and a single dose of an antifungal medication.…”
Section: Pancreas Transplantation (Table 1)mentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of enhanced recovery after surgery (ERAS) protocols have improved post‐operative pain management by incorporating a multimodal, multidisciplinary approach. Patient education, utilization of multiple analgesics, and thoughtful discharge planning have all been demonstrated to reduce opioid use while achieving adequate post‐operative pain control 1–4 . While opioid reduction is not the primary goal of ERAS protocols, limiting opioid use and prescribing has both societal and individual patient benefits 5–7 …”
Section: Introductionmentioning
confidence: 99%